The 'Green Revolution' destroying biodiversity? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Growing diversity edited by David Cooper, Renee Vellve and Henk Hobbelink 1992 192pp ISBN 1 85339 119 0 Pbk UKL9.95 IT Publications Ltd 103-105 Southampton Row London WC1B 4HH, UK